Co-crystals of non-steroidal anti-inflammatory drugs (NSAIDs): Insight toward formation, methods, and drug enhancement - Nascimento, André L.C.S. [UNESP]; Fernandes, Richard P. [UNESP]; Charpentier, Maxime D.; ter Horst, Joop H.; Caires, Flávio J. [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2021)
Pharmaceutical co-crystals have been explored by many researchers as a strategy to optimize physicochemical properties of solid-state drugs. Their improvements of solubility, bioavailability, and the reduced tendency for phase transformation occurrence, are factors that highlight benefits of pharmaceutical co-crystals among other solid forms. According to the Biopharmaceutical Classification System (BCS), non-steroidal anti-inflammatory drugs (NSAIDs) are class II drugs, which have low aqueous solubility and therefore co-crystallization has the potential to optimize NSAID product properties. In this review, we highlight the recent progress made on NSAIDs co-crystals, their co-formers, synthesis, methods and use, while we underline some promising results on in vitro and in vivo co-crystal properties. A celecoxib-tramadol co-crystal reaches phase III clinical trials, showing greater analgesic activity than both individual APIs. The aqueous solubility of the co-crystal formed between L-proline and diclofenac is very high in comparison with the pure drug. Naproxen co-crystals with urea and thiourea have an increase of drug release of almost 60%. Co-crystal design brings a new perspective in drug development since the co-former used can also be a biologically active component allowing to combine different anti-inflammatory drugs, which have an incredible spectrum of application due to the analgesic, anti-pyretic and anti-inflammatory properties.
Keywords: Bioavailability; Co-crystal discovery; NSAIDs; Pharmaceutical co-crystals; Supramolecular synthons